2006
DOI: 10.1111/j.1365-2486.2006.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Climatic signals in growth and its relation to ENSO events of two Prosopis species following a latitudinal gradient in South America

Abstract: Semiarid environments throughout the world have lost a major part of their woody vegetation and biodiversity due to the effects of wood cutting, cattle grazing and subsistence agriculture. The resulting state is typically used for cattle production, but the productivity of these systems is often very low, and erosion of the unprotected soil is a common problem. Such dry-land degradation is of great international concern, not only because the resulting state is hardly productive but also because it paves the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 43 publications
2
27
1
3
Order By: Relevance
“…Dendrochronological studies using Prosopis have presented different levels of correlation between their tree-ring series; this large variability likely reflects the broad plasticity and adaptability of Prosopis trees to different environmental conditions (Villalba et al 2000). For example, López et al (2006) developed three chronologies for Prosopis pallida HBK in Peru and one of Prosopis chilensis (Mol.) Stuntz in Chile.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrochronological studies using Prosopis have presented different levels of correlation between their tree-ring series; this large variability likely reflects the broad plasticity and adaptability of Prosopis trees to different environmental conditions (Villalba et al 2000). For example, López et al (2006) developed three chronologies for Prosopis pallida HBK in Peru and one of Prosopis chilensis (Mol.) Stuntz in Chile.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is no general consensus that explains the low natural regeneration rates of individuals of the genus Prosopis (Carevic et al, 2012). Previous studies have concluded that regeneration rates are extremely low, mainly due to periods in which the ENSO (El Niño-Southern Oscillation) phenomenon is active, which induces erratic behavior in the natural germination of seeds (López et al, 2006). During the ENSO phenomenon it appears that the main physiological trait that supports plant survival is deeper root growth (Squeo et al, 2007).…”
Section: Ecophysiological Studies As Tools Of Conservationmentioning
confidence: 95%
“…The effects of rainfall variation in semi-arid Brazil, taking into account population growth and demands for land use have been modeled by Barbieri et al (2010) and Krol and Bronstert (2007). Intense dry events have been attributed to "El Niño" (SILVA, 2004), and can be recognized by examination of growth ring patterns in dry forest species (BRIENEN et al, 2010;FICHTLER et al, 2004;GEBREKIRSTOS et al, 2008;LOPEZ et al, 2006;RODRIGUEZ et al, 2005).…”
Section: Tenuiflora Grew At Least 44% More In the Open Areas With mentioning
confidence: 99%
“…Therefore, there are two causes that could explain the different behavior in this area. Lopez et al (2006) studied the growth response to rainfall, temperature and El Niño (ENSO) in two naturally occurring species along the latitudinal gradient from Peru (Prosopis pallida) to central Chile (Prosopis chilensis). Despite the distance between the locations, the growth of the two species had similar positive correlations with rainfall.…”
Section: Tenuiflora Grew At Least 44% More In the Open Areas With mentioning
confidence: 99%